BASIC STANDARD ELEMENTS IN LOGISTICS: BASIC STANDARD ELEMENTS IN LOGISTICS - Bogdanov, Andrey; Velcheva-Todorova, Pety (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The paper examines the relationship between standardization and logistics, through the application of the most - widely used methods for transporting goods by means of different transportation. It also deals with the issues of securing cargo, grippers for loading - unloading work and storage systems as parts of the logistic system.